Relogement des quartiers informels et conflits pour l’espace public. Le cas de la nouvelle ville d’Ali Mendjeli (Constantine, Algérie) - Brahim Benlakhlef; Pierre Bergel (Les Cahiers d’EMAM)
Inside the great Constantina, a new part of the city called Ali Mendjeli receive a large number of families removed from sensitive or informal housings which roped off the historic center. Public authorities give to those families new and comfortable apartments. Consequently, they consider that social support is unnecessary while those forced relocations have been accompanied by tensions and protests when informal housings were brutally destroyed. Since the beginning of 2014, some parts of Ali Mendjeli are affected by violence which takes sometimes a shocking turn. Those violent periods concern groups of young men recently resettled in Ali Mendjeli with their families and coming from different informal areas which have been destroyed. Violence is caused by competition between football supporters or to take control of informal car park zones. In those cases, local public places look like issues for the balance of power between those different groups. They also appear like a scene for the battle. Elder population, supposed to embody a traditional power on younger, can’t ease the most troubled spirits, no more than official representatives. Consequently, violence is growing up into certain parts of Ali Mendjeli, which making it hard to maintain ordinary city life and business activity.